INVESTIGATING INDONESIAN EFL LEARNERS’ CRITICAL THINKING: CURRENT STATE AND FUTURE DIRECTIONS - Eleazar Evan Moeljono; Alies Poetri Lintangsari (English Review: Journal of English Education, 2021)
This research aims to investigate the critical thinking skills of 86 Indonesian English as a Foreign Language (EFL) learners who are prepared to be English teachers using an adapted questionnaire measuring critical thinking skills. This research uses a descriptive quantitative research design to examine the critical thinking skills of Indonesian EFL learners. It reveals the ability of Indonesian EFL learners’ critical thinking skills through a diagnostic test which results in a moderate level, implying that the strategies to embed critical thinking in an EFL classroom setting need to be improved. This eventually might lead to a wide gap between the existing teacher's competence and the expected qualities. This research argues the diagnosis of critical thinking state in Indonesia’s pre-service English teachers and the future directions to leverage critical thinking skills.